1991
DOI: 10.1042/bj2730679
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous regulation of constitutive thrombomodulin or inducible tissue-factor activities on the surface of human saphenous-vein endothelial cells in culture following stimulation by interleukin-1, tumour necrosis factor, thrombin or phorbol ester

Abstract: Thrombomodulin and tissue-factor activities were measured on the surface of confluent human saphenous-vein endothelial cells (HSVEC) cultivated in 96-multiwell plates. Thrombomodulin activity was measured in the presence of purified human thrombin (2.2 nM) and protein C (65 nM). Tissue-factor activity was measured with purified human Factor VII (5 nM) and Factor X (400 nM). Generated activated protein C and Factor Xa released in the supernatant were assayed with chromogenic substrates. Resting cells exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 49 publications
7
60
1
Order By: Relevance
“…The TF activity was normalized to the cell counts from the same well and expressed as,aU of TF/10 s ¢¢11s. expression of TF which reached a maximum around 6 h. These results confirm previous observations showing that these compounds induce endothelial cell procoagulant activity while suppressing cell-surface anticoagulant activity [11,12]. For both ABAE and monocytes, TF expression in control wells did not vary significantly over the 24-h incubation period and the passage number had no effect on the procoagulant activity of the various inflammatory mediators (not shown).…”
Section: Determination Of Tlssue Factor Activity On the Cellssupporting
confidence: 79%
“…The TF activity was normalized to the cell counts from the same well and expressed as,aU of TF/10 s ¢¢11s. expression of TF which reached a maximum around 6 h. These results confirm previous observations showing that these compounds induce endothelial cell procoagulant activity while suppressing cell-surface anticoagulant activity [11,12]. For both ABAE and monocytes, TF expression in control wells did not vary significantly over the 24-h incubation period and the passage number had no effect on the procoagulant activity of the various inflammatory mediators (not shown).…”
Section: Determination Of Tlssue Factor Activity On the Cellssupporting
confidence: 79%
“…7 However, the signaling mechanisms underlying tissue factor expression are not fully understood. Here, we showed that thrombin-induced tissue factor expression is regulated positively by Rho/Rho-kinase and p38 MAP kinase.…”
Section: Discussionmentioning
confidence: 99%
“…5 Indeed, thrombin induces platelet aggregation 6 and tissue factor expression. 7 Thus, thrombin is a key modulator of this positive feedback mechanism of thrombus formation. However, the signaling pathways responsible for thrombin-induced tissue factor expression remain unclear.…”
mentioning
confidence: 99%
“…[16][17][18] Another inflammatory cytokine, interleukin 1 has also been shown to reduce thrombomodulin activity on endothelial cells. 19,20 Another important pathway linking inflammation and coagulation is the fibrinolytic system. Plasminogen is converted to plasmin by tissue-type plasminogen activator (t-PA) or urokinase-type plasminogen activator (u-PA), both of which are regulated by plasminogen activator inhibitor-1 (PAI-1).…”
Section: Mechanisms Linking Inflammation and Venous Thrombosismentioning
confidence: 99%